Framing Sexual Refusal Experiences among Emerging Adult Women: Politeness Theory in Unscripted Territory. Issue 1 (2nd January 2022) - Dalton, Elizabeth D.
ABSTRACT: Although sexual refusal can be a complex, face-threatening interpersonal exchange, the nuances of these encounters are often overlooked by sexual and consent education messages. To examine this phenomenon more closely, the current study analyzed emerging adult college women's descriptions of past sexual refusal episodes to better understand how they frame their sexual refusal experiences in terms of face needs and risks, and the cultural roles and scripts are reflected in the descriptions of sexual refusal. Two primary frames emerged through the analysis: Refusal as successful and refusal as failure. Thematic characteristics within each frame are examined in terms of politeness theory and face needs, as well as the broader cultural sexual scripts that impact norms surrounding who, how, when, and if sexual refusal can occur. Theoretical implications include consideration of how the discourse of U.S. sexual consent education emerges in the findings, the limitations of politeness theory in understanding sexual refusal, and suggest alternative theoretical approaches.